The impact of the Roman Empire on landscapes : proceedings of the fourteenth Workshop of the International Network Impact of Empire (Mainz, June 12-15, 2019) - Horster, Marietta; Hächler, Nikolas (Impact of Empire (Roman Empire, 27 B.C.-A.D. 406),, 2021)
"Volume presents the results of the fourteenth workshop of the international network 'Impact of Empire'. It focuses on the ways in which Rome's dominance influenced, changed, and created landscapes, and examines in which ways (Roman) landscapes were narrated and semantically represented. To assess the impact of Rome on landscapes, some of the twenty contributions in this volume analyse functions and implications of newly created infrastructure. Others focus on the consequences of colonisation processes, settlement structures, regional divisions, and legal qualifications of land. Lastly, some contributions consider written and pictorial representations and their effects. In doing so, the volume offers new insights into the notion of 'Roman landscapes' and examines their significance for the functioning of the Roman empire"--